INVESTIGASI KADAR HEMOGLOBIN PASIEN CANCER PAYUDARA PRE DAN POST KEMOTERAPI - Pitri, Angela Dwi; Andri, Florensius; Kurniasih, Dwi; Sari, Della Putria (Jurnal Keperawatan dan Kesehatan, 2024)
Anemia refers to a decrease in serum hemoglobin concentration to pathological levels where hemoglobin level in women is <12 g/dl and in men <14 g/dl. More than 40% of cancer patients undergoing chemotherapy are subjected to anemia. As chemotherapy drugs are unable to distinguish between normal and neoplastic cells, their destructive nature results in a reduced number of red blood cells through the hemolysis process. The principles of chemotherapy are required to maintain a number of normal cells to avoid unintended side effects. This study aimed to investigate the hemoglobin levels before and after chemotherapy. The method of this study was qualitative, using a case study approach. The study sample consisted of three individuals, and the hemoglobin levels were assessed using the EasyTouch hemoglobinometer. The data were processed using Colaizzi’s analysis method: reading, meaning formulation, and theming. The results of this study were presented in three themes: (1) anemia occurred due to oxidative stress, (2) a decrease in the number of red blood cells caused by lysis; and (3) PRC transfusion as a way to overcome anemia. It can be concluded that a decrease in the number of red blood cells is inevitable. Therefore, patients are advised to get sufficient rest, increase their intake of nutritious food, and consume iron vitamins.